PARENT OR GUARDIAN KNOWLEDGE OF BIOLOGICAL NEWBORN SCREENING - Dias Cordeiro, Rafael; Santos Landim, Fernanda; Ferreira Lima, Viviane; Luisa Cardoso Oliveira, Maria; Moreira Fagundes Veloso, Fernanda (Health and Society, 2024)
The objective of this study was to analyze the level of knowledge of parents or guardians about the biological newborn screening test. An integrative literature review study was conducted using the secondary databases Virtual Health Library, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online and Online System for Search and Analysis of Medical Literature based on the specific descriptors retrieved in the Health Sciences Descriptors. In general, it was identified that parents or guardians have limited knowledge about biological newborn screening, restricting themselves to some diseases, resulting in delays or risk of not performing the exam, also causing risks to the child’s health. Efforts are needed from health professionals so that, throughout the prenatal period, pregnant women and family members are exposed to up-to-date and evidence-based information about the test, both in clinical consultations and in systematic health education actions in collective groups and also in the waiting room and other spaces of the unit and territory.